2013
DOI: 10.1016/j.neuroscience.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of neuronal function in the amygdaloid region reduces tail artery blood flow alerting responses in conscious rats

Abstract: Few studies have investigated whether neuronal function in the amygdaloid complex is necessary for the occurrence of the cardiovascular response to natural (unconditioned) environmental threats. In the present investigation in conscious unrestrained Sprague-Dawley rats we inactivated neuronal function in the amygdaloid complex acutely (bilateral muscimol injections) or chronically (unilateral or bilateral ibotenic acid injections) and measured the effect on sudden falls in tail artery blood flow elicited by no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…Our present study and our earlier investigations in rabbits and rats (6,14,36,63,64) demonstrate that salient or emotional events also vigorously reduce thermoregulatory cutaneous blood flow, and this is also the case in humans (6,13,16,22). Emotional hyperthermia also occurs in humans, as first convincingly demonstrated by Renbourn (48).…”
Section: Perspectives and Significancesupporting
confidence: 88%
“…Our present study and our earlier investigations in rabbits and rats (6,14,36,63,64) demonstrate that salient or emotional events also vigorously reduce thermoregulatory cutaneous blood flow, and this is also the case in humans (6,13,16,22). Emotional hyperthermia also occurs in humans, as first convincingly demonstrated by Renbourn (48).…”
Section: Perspectives and Significancesupporting
confidence: 88%
“…When the measures were performed several hours later, it appeared that several subjects from the "high" group moved to the "low" group and vice versa, and authors suggested that in humans finger blood flow tends to follow a "all or none" pattern rather than gradual changes [5]. While we were unable to identify any other studies where finger temperature of finger blood flow were assessed for relatively long (several hours) periods, blood flow in thermoregulatory vascular beds in animal (ear pinna artery in rabbits and tail artery in rats) is controlled in exactly this way: it remains either predominantly high or predominantly low for extended periods of time [27,45]. Mechanistically this could be explained by the likelihood that arterio-venous anastomoses abundantly present in all three vascular beds and involved in heat dissipation are either mainly opened or mainly closed.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, such nonnoxious brief stimuli evoke only small and transient increases in arterial pressure and little or no changes in blood flow to the mesenteric, renal, and hindlimb vascular beds (109,162), indicating that the sympathetic outflow to the cutaneous vascular bed is rather selectively activated by mild alerting stimuli. Consistent with this, alerting stimuli in humans reliably increase cutaneous sympathetic activity (156).…”
Section: Pattern Of Cardiovascular and Respiratory Responses To Stresmentioning
confidence: 96%
“…In animals, brief alerting stimuli such as an unexpected noise or light will evoke immediate autonomic and respiratory responses, characterized by strong cutaneous vasoconstriction and respiratory activation (17,18,84,109,161). In contrast, such nonnoxious brief stimuli evoke only small and transient increases in arterial pressure and little or no changes in blood flow to the mesenteric, renal, and hindlimb vascular beds (109,162), indicating that the sympathetic outflow to the cutaneous vascular bed is rather selectively activated by mild alerting stimuli.…”
Section: Pattern Of Cardiovascular and Respiratory Responses To Stresmentioning
confidence: 99%
See 1 more Smart Citation